2017
DOI: 10.1177/1557988317728353
|View full text |Cite
|
Sign up to set email alerts
|

Men’s Mental Health Promotion Interventions: A Scoping Review

Abstract: There is an increasing need for mental health promotion strategies that effectively engage men. Although researchers have examined the effectiveness of diverse mental wellness interventions in male-dominated industries, and reviewed suicide prevention, early intervention, and health promotion interventions for boys and men, few have focused on sex-specific program effects. The purpose of this review was to (a) extend the previous reviews to examine the effectiveness of mental health promotion programs in males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
53
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 53 publications
(135 reference statements)
2
53
0
1
Order By: Relevance
“…We developed the materials based on knowledge from previous research. However, most previous studies on male health promotion focuses on specific intervention settings and were delivered in face‐to‐face settings . Most research on mental health communication with men addresses depression and other mental health problems but does not explicitly look at suicide .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We developed the materials based on knowledge from previous research. However, most previous studies on male health promotion focuses on specific intervention settings and were delivered in face‐to‐face settings . Most research on mental health communication with men addresses depression and other mental health problems but does not explicitly look at suicide .…”
Section: Discussionmentioning
confidence: 99%
“…42,52 Most research on mental health communication with men addresses depression and other mental health problems but does not explicitly look at suicide. 42,53 Research evidence stems from a variety of western cultures, dominated by studies from the UK and the US 52,54,55 and few are multilevel interventions including online media. With online health interventions of the rise, 56,57 our study is an important addition in this area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, men are consistently less likely than women to seek professional mental health support, regardless of age, ethnicity, and social backgrounds . This indicates an increasing need for mental health promotion strategies that are effective in both engaging and assisting men …”
Section: Introductionmentioning
confidence: 99%
“…Although men are often reluctant to participate in traditional mental health treatments (eg, therapy and medication), studies have found men will seek help if it is accessible, appropriate, and engaging . This is an important area of future research, particularly with scholars recently suggesting that it may be more fruitful to improve men's mental health indirectly through lifestyle interventions …”
Section: Introductionmentioning
confidence: 99%